DESAIN PERANCANGAN MESIN PEMOTONG KENTANG MULTIFUNGSI - Arif Rohman (ELEMEN : JURNAL TEKNIK MESIN, 2025)
We often encounter potatoes in traditional and modern markets. Potatoes are very easy to process into various kinds of food, one of which is French fries. For this reason, this research has produced a multifunctional potato cutting machine design that is time efficient, fast in cutting potatoes, and is also a portable machine. The results of this multifunctional potato cutting machine design resulted in the design of machine components such as a potato funnel hopper with dimensions of 300 mm x 80 mm x 222 mm, a potato pusher with dimensions of 80 mm x 114 mm, and the main frame of the machine with dimensions of 421 mm x 300 mm x 380 mm. Then there are 3 variants of cutting knives consisting of flat, long/stick and soft cutting knives. Apart from that, the knife driver used is an electric motor and other drive transmission. Overall, the results of this design produce a design drawing for a potato cutting machine with dimensions of 421 mm x 300 mm x 544 mm.